Yellowknife, Northwest Territories - Northwest Survey Corporation Limited (1969)
This is a 1969 orthophotomap of Yellowknife, Northwest Territories. Scale approximately 1:12,000. Shows points of interest, such as fire stations, museums, city hall, federal buildings, hotels, churches, hospitals, schools, parks, and more. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .